Navigating the road ahead : BMW's path in the electrified vehicle market - Jia, Yankun; Richardson, Jacob; Gentry, Richard J. (London : SAGE Publications: SAGE Business Cases Originals, 2021)
Among the major automakers, BMW has long been a successful premier seller of luxury automobiles. In recent years the market has been changing, impacting BMW. In the past decade, electrification has brought a paradigm shift to the automotive market in both engineering and construction. Automakers are racing to develop electrified vehicles amidst the impact of global trade policies and new laws and regulations that require new standards such as reduced emissions and autonomous driving functionalities. How BMW responds to the changes and modifies its strategies to meet customer demands, will determine their success in growing market segments and emerging markets that did not have access to their product in decades past. What should BMW do to maintain its "ultimate driving machine" experience in the electrification process while abiding tightening emission regulations? How does BMW survive in the crisis of anti-globalization movements?
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bayerische Motoren Werke -- Case studies; Automobile industry and trade -- Case studies; Strategic planning -- Case studies; Electric vehicle industry -- Case studies